2022
DOI: 10.3389/fcell.2022.831215
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs as Orchestrators of CD4+ T-Cell Fate

Abstract: CD4+ T cells differentiate towards different subpopulations through the regulation of lineage-specific cytokines and transcription factors, which flexibly respond to various immune challenges. However, considerable work has demonstrated that the CD4+ T-cell differentiation mechanism is complex and not limited to transcription factors and cytokines. Long noncoding RNAs (lncRNAs) are RNA molecules with lengths exceeding 200 base pairs that regulate various biological processes and genes. LncRNAs have been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
(108 reference statements)
1
4
0
Order By: Relevance
“…23,34,35 Although the underlying mechanisms by which IFNG-AS1 regulates Ifng expression in Th1 cells has yet to be completely defined, the possible influence of T-bet on IFNG-AS1 expression denotes further implications for the crucial roles of T-bet in conjunction with IFNG-AS1 in Th1 cell differentiation and function. 21,36 In line with these findings, our results regarding concurrent expression of IFNG-AS1 and Tbx21 in the presence of HLA risk alleles might be indicative for the dominance of Th1 cell subset in SLE patients carrying susceptible HLA alleles. However, due to the expression of Tbx21 in multiple lineages of lymphocytes, our results should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…23,34,35 Although the underlying mechanisms by which IFNG-AS1 regulates Ifng expression in Th1 cells has yet to be completely defined, the possible influence of T-bet on IFNG-AS1 expression denotes further implications for the crucial roles of T-bet in conjunction with IFNG-AS1 in Th1 cell differentiation and function. 21,36 In line with these findings, our results regarding concurrent expression of IFNG-AS1 and Tbx21 in the presence of HLA risk alleles might be indicative for the dominance of Th1 cell subset in SLE patients carrying susceptible HLA alleles. However, due to the expression of Tbx21 in multiple lineages of lymphocytes, our results should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 84%
“…23,34,35 Although the underlying mechanisms by which IFNG-AS1 regulates Ifng expression in Th1 cells has yet to be completely defined, the possible influence of T-bet on IFNG-AS1 expression denotes further implications for the crucial roles of T-bet in conjunction with IFNG-AS1 in Th1 cell differentiation and function. 21,36…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation reported that overexpression of IFNG‐AS1 in CD4 + T cells led to elevated inflammatory cytokines secretion, reduced levels of anti‐inflammatory cytokines and increased differentiation to Th1/Th17 cells through targeting miR‐125a and upregulating IL‐23R 145 . The lncRNA Th2‐LCR found to regulate the production of cytokines associated to differentiation of Th2 cells by translocating to IL‐4, IL‐5 and IL‐13 coding genes, and its knockdown reduced H3K4 methylation of the IL‐4 and IL‐13 promoters 146,147 . Several lncRNAs have been reported to modulate the T cells function.…”
Section: Noncoding (Nc) Rnas and Immunosenescencementioning
confidence: 97%
“…145 The lncRNA Th2-LCR found to regulate the production of cytokines associated to differentiation of Th2 cells by translocating to IL-4, IL-5 and IL-13 coding genes, and its knockdown reduced H3K4 methylation of the IL-4 and IL-13 promoters. 146,147 Several lncRNAs have been reported to modulate the T cells function. For instance, lncRNA NRON regulates the expression of nuclear factor of activated T cells (NFAT1) that is required for IL-2 production as well as naive T cell proliferation and survival.…”
Section: Lncrna Regulated T Cell Development Differentiation and Plas...mentioning
confidence: 99%
“…LncRNAs are important contributors to immune homeostasis and effector functions ( 14 ) and regulate T helper (Th) cell differentiation ( 15 ). For example, linc-MAF4, a Th1-specific lncRNA in humans, limits Th2 differentiation by negatively regulating MAF4, a Th2-specific TF ( 16 ).…”
mentioning
confidence: 99%